PENDAPATAN DAN RISIKO USAHATANI JAHE DI KECAMATAN PENENGAHAN KABUPATEN LAMPUNG SELATAN - Julaily Eka Saputra; Fembriarti Erry Prasmatiwi; R Hanung Ismono (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aimed to assess the income, the risk of farming, and the correlation risk toward income of ginger farming.  This research was conducted by survey method, involving 60 farmer respondents with four years farming experiences.  The data of this research was collected in Juni – Juli 2016.  The third objective was analyzed by multiple linear regression and the other analysis used in this research was descriptive and quantitative analysis.  The results showed that the income of ginger farming was Rp28,038,043.74/ha and the value of R/C on total cost 1.68. The risk of ginger farming was on high category in which CV value was 0.51.  The risk of ginger farming had significantly influence the income.Key words: ginger, income, production, risk